Development of Children’s Cyber Security Competencies in Estonia - Lorenz, Birgy; Kikkas, Kaido; Osula, Kairi (Learning and Collaboration Technologies. Learning and Teaching, 2018)
In recent years, development of digital competencies has become a major task in the education system as various technologies and Internet have become a staple in ordinary classroom. Safety, both in the physical and digital world, is supposed to keep pace with these developments. In Estonia, the new curricula developed for informatics and related subjects include digital safety. In this study, we have looked at the competencies in Grades 4–9. In our study, 10581 students participated from 40% focus group schools, topics were fraud, data, health, freedom, and online reputation. Based on the results, we will outline the threat groups that the schools and teachers should focus on in Estonia and others that have been overstressed by the awareness training so far. These results will hopefully help to develop better learning materials and tests for Grades 4–9 in order to improve their digital safety competencies.